2016
DOI: 10.2522/ptj.20160099
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of Force Platform Measures of Balance Impairment in Individuals With Parkinson Disease

Abstract: This study's findings provide support that FP measures are reliable and valid tests of balance impairment in people with PD. Disease severity was significantly associated with SOT and MCT measures, perhaps reflecting that these tests are meaningful indicators of decline in postural control with disease progression. Force platform measures may provide valuable quantitative information about underlying balance impairments in people with PD to guide therapeutic interventions for fall risk reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
3

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 44 publications
1
27
0
3
Order By: Relevance
“…This study was part of a larger study examining the reliability and concurrent validity of FP measures in individuals with PD, with detailed description of the full study's methods published by Harro et al [31]. Data were collected in the university's biomechanics laboratory, a quiet, controlled environment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was part of a larger study examining the reliability and concurrent validity of FP measures in individuals with PD, with detailed description of the full study's methods published by Harro et al [31]. Data were collected in the university's biomechanics laboratory, a quiet, controlled environment.…”
Section: Methodsmentioning
confidence: 99%
“…These FP measures are also supported as reliable and valid measures of underlying postural control deficits across neurological populations [2730]. Specific to the PD population, Harro et al [31] reported excellent test-retest reliability for these FP measures, and fair to moderate correlation between the SOT and LOS test and clinical balance measures.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the numerical difference between CD adults and persons with PD was observed in ES(CON5), which was 21.8, much larger than the established minimal clinical difference of 13.33.24 Several studies in persons with PD revealed similar results, with greater deficits in ES (CON5) and SA (VES) ratio scores than ES and SA scores in their respective studies. 23,25 To shed light on the differences between both groups, all CS for CD elderly adults were above the cutoff score for falls (cut off score CS<67)3, while 50% of persons with PD scored below the cut off score. Given these results, the 60-70 year old individuals with PD display substantial deficits across all conditions in comparison to same age healthy CD adults.…”
Section: Discussionmentioning
confidence: 99%
“…22 Test-retest reliability of the SOT stated good to excellent reliability (ICC=.78-.90) for individuals with PD. 23 Testing of participants took place at California State University, Fresno in the Department of Physical Therapy laboratory. For safety purposes, each participant donned a harness prior to the initiation of the SOT.…”
Section: Instrumentationmentioning
confidence: 99%
“…In general, maintaining a normative eased upright stance requires the symmetric distribution of body weight; when challenged, the resultant anterior-posterior or bilateral compensatory motion can be captured using a force platform to record changes in the body's center of pressure [27], [28]. For the present work, this assessment was achieved using a customized platform system developed at the Department of Solid Mechanics, Lund Institute of Technology in Sweden [3].…”
Section: B Posturography Measurementmentioning
confidence: 99%